[OP.4B.07] EXAGGERATED BLOOD PRESSURE RESPONSE DURING HANDGRIP EXERCISE IN MASKED HYPERTENSIVE: CAN IT BE USED AS AN ADDITIONAL SCREENING TOOL?. (September 2016) - Dipla, K.; Triantafyllou, A.; Koletsos, N.; Sachpekidis, V.; Poulios, P.; Gkaliagkousi, E.; Zafeiridis, A.; Douma, S.
Abstract : Objective: Masked hypertensives (MH) are at increased cardiovascular risk and target organ damage. Despite a growing number of studies suggesting that early identification of these patients is crucial, a 24 h ambulatory blood pressure (BP) or proper home BP monitoring are not always feasible. An exaggerated BP response during dynamic exercise testing (duration ∼9–15 min) has been used as an additional screening tool to identify suspected systolic MH. However, MH especially in young people, is often characterized by an elevated diastolic BP. Static handgrip exercise elicits augmented sympathetic stimulation causing greater and more rapid (<3 min) increases in both systolic and diastolic BP than dynamic exercise. Thus, we aimed at examining whether MH will exhibit an exaggerated BP response during a 3-min, low intensity handgrip exercise test than normotensive individuals. Design and method: Sixteen newly diagnosed MH and 26 normotensives, aged 44.3 ± 11.7 yrs, without other known cardiovascular disease and under no antihypertensive treatment participated in the study. Following a physical examination, vascular stiffening evaluation, echocardiography, and ambulatory BP monitoring, each participant underwent a testing protocol consisting of a seated rest (baseline), a 3-min handgrip exercise at 30% maximal voluntary contraction (MVC), and a 3-min recovery. Beat-by-beat blood pressure (Finapres) was continuously monitored. Results: There were no significant differences between groups in age, BMI, and MVC. Office BP were within normal range in both groups (128.1 ± 6.7/81.0 ± 7.9 and 119.5 ± 8.7/77.3 ± 6.7 mmHg, in masked-HYP and normotensives, respectively). During baseline, no differences between groups were observed in systolic and diastolic BP. However, average BP responses during handgrip were greater in MH than in normotensives (176.3 ± 12.7/100.8 ± 6.2 vs. 158.9 ± 15.0/92.1 ± 8.4 mmHg, respectively; p < 0.05). MH exhibited an augmented BP response from the 1st minute of handgrip exercise vs. normotensives (162.3 ± 3.3/93.7 ± 11.3 vs. 144.0 ± 2.6/84.4 ± 8.6 mmHg). These 1st-minute handgrip BP responses were positively correlated (r = 0.45–0.65; p < 0.05) with ambulatory day- and 24 hour- BP. Within the MH group, significant correlations (r = 0.40–0.81; p < 0.05) were observed between the 1st-minute-handgrip responses and diastolic aortic-, peripheral-, and ambulatory- BP, carotid IMT, and pulse wave velocity measurements. Conclusions: A brief low intensity handgrip test can be used as an additional screening tool in indentifying patients with masked systolic and/or diastolic hypertension.